Memory Analysis of macOS Page Queues. (July 2020) - Case, Andrew; Maggio, Ryan D.; Manna, Modhuparna; Richard, Golden G.
Abstract: Memory forensics is the examination of volatile memory (RAM) for artifacts related to a digital investigation. Memory forensics has become mainstream in recent years because it allows recovery of a wide variety of artifacts that are never written to the file system and are therefore not available when performing traditional filesystem forensics. To analyze memory samples, an investigator can use one of several available memory analysis frameworks, which are responsible for parsing and presenting the raw data in a meaningful way. A core task of these frameworks is the discovery and reordering of non-contiguous physical pages in a memory sample into the ordered virtual address spaces used by the operating system and running processes to organize their code and data. Commonly referred to as address translation, this task requires a thorough understanding of the memory management mechanisms of the hardware architecture and operating system version of the device from which the memory sample was acquired. Given its critical role in memory analysis, there has been significant interest in studying the operating system mechanisms responsible for allocating and managing physical pages so that they can be accurately modeled by memory analysis frameworks. The more thoroughly the page handling mechanisms are modeled in memory forensics tools, the more pages can be scrutinized during memory analysis. This leads to more artifacts being reconstructed and made available to an investigator. In this paper, we present the results of our analysis of the macOS page queues subsystem. macOS tracks pages in a number of different states using a set of queues and as we will illustrate, the reconstruction of data from these queues allows a significant number of memory pages to be analyzed that are currently ignored by memory forensics tools. Through incorporation of these artifacts into analysis, memory analysis frameworks can present an even richer set of artifacts and data to investigators than ever before.